Role of negatively charged amino acids in beta 4 F-loop in activation and desensitization of alpha 3 beta 4 rat neuronal nicotinic receptors - Lindovský, Jirí; Kaniaková, Martina; Svobodová, Lucie; Vyskocil, Frantisek; Krůsek, Jan (Biochimica et biophysica acta, 2008)
The role of negatively charged amino acids in the F-loop of the beta 4 subunit in channel activation and desensitization was studied using the patch-clamp technique. The selected amino acids were changed to their neutral analogs via point mutations. Whole-cell currents were recorded in COS cells transiently transfected with the alpha 3 beta 4 nicotinic acetylcholine receptor. The application of acetylcholine (ACh), nicotine (Nic), cytisine (Cyt), carbamylcholine (CCh) and epibatidine (Epi) to cells clamped at -40 mV produced inward currents which displayed biphasic desensitization. The EC50 of Epi and Nic were increased by a factor of 3-6 due to mutations D191N or D192N. Only Epi remained an agonist in the double-mutated receptors with EC50 increased 17-fold. The interaction of the receptors with the competitive antagonist (+)tubocurarine (TC) was weakened almost 3-fold in the double-mutated receptors. The mutations increased the proportion of the slower desensitization component and increased the response plateau, resulting in decreased receptor desensitization. The double mutation substantially accelerated the return from long-term desensitization induced by Epi.
Keywords: nikotin; COS Cells; vztahy mezi strukturou a aktivitou; Amino Acids; Molecular Sequence Data; Protein Subunits; sekundární struktura proteinů; podjednotky proteinů; Mutation; Structure-Activity Relationship; Bridged Bicyclo Compounds, Heterocyclic; zvířata; nikotinoví agonisté; Rats; Nicotine; bicyklické sloučeniny heterocyklické; Tubocurarine; tubokurarin; Neurons; Sequence Alignment; COS buňky; Pyridines; sekvence aminokyselin; Nicotinic Agonists; Protein Structure, Secondary; sekvenční seřazení; Kinetics; krysa rodu Rattus; Chlorocebus aethiops; molekulární sekvence - údaje; kinetika; pyridiny; Animals; Amino Acid Sequence; Receptors, Nicotinic; neurony; mutace; aminokyseliny; Cercopithecus aethiops; nikotinové receptory